2020
DOI: 10.1039/c9cc08696j
|View full text |Cite
|
Sign up to set email alerts
|

Purely inorganic frameworks based on polyoxometalate clusters with abundant phosphate groups: single-crystal to single-crystal structural transformation and remarkable proton conduction

Abstract: A pure-inorganic framework 1 underwent a SCSC transformation to form a new framework 1′, which has high proton conductivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
29
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…POMs can be considerably altered when mixed with organic moieties including ionic liquids or quaternary ammonium salts [54]. Certain POMs exhibit luminous properties; others, which include ferromagnetic transition metal atoms with free electrons, display anomalous magnetic characteristics and are being studied as nano-computer storage systems.…”
Section: Principal Properties Of Pomsmentioning
confidence: 99%
“…POMs can be considerably altered when mixed with organic moieties including ionic liquids or quaternary ammonium salts [54]. Certain POMs exhibit luminous properties; others, which include ferromagnetic transition metal atoms with free electrons, display anomalous magnetic characteristics and are being studied as nano-computer storage systems.…”
Section: Principal Properties Of Pomsmentioning
confidence: 99%
“…Recently, crystalline molecular materials including POMs [36–38] and coordination polymers (e.g. metal‐organic frameworks) [46] have received immense attention as solid‐state proton‐conductors, owing to their possible role as solid‐state electrolytes.…”
Section: Figurementioning
confidence: 99%
“…This is based on pioneering studies which have demonstrated the use of POMs for proton conduction under harsh conditions incompatible with organic proton exchange membranes [29–34] . Several strategies have been employed to introduce proton conductivity in POMs, including introduction of surface protonation sites, [29, 35] design of hydrophilic channels [36, 37] and spatially confined hydrogen‐bonded network formation, often in the pores of framework materials [30, 38] . In particular, the design of polymeric POM aggregates and exploration of their proton conduction could trigger synergisms between inorganic and bio‐chemistry, as in nature, bio‐polymers (e.g.…”
Section: Figurementioning
confidence: 99%
“…This is based on pioneering studies which have demonstrated the use of POMs for proton conduction under harsh conditions incompatible with organic proton exchange membranes. [29][30][31][32][33][34] Several strategies have been employed to introduce proton conductivity in POMs, including introduction of surface protonation sites, [29,35] design of hydrophilic channels [36,37] and spatially confined hydrogenbonded network formation, often in the pores of framework materials. [30,38] In particular, the design of polymeric POM aggregates and exploration of their proton conduction could trigger synergisms between inorganic and bio-chemistry, as in nature, bio-polymers (e.g.…”
mentioning
confidence: 99%
“…Recently, crystalline molecular materials including POMs [36][37][38] and coordination polymers (e.g. metal-organic frameworks) [46] have received immense attention as solidstate proton-conductors, owing to their possible role as solidstate electrolytes.…”
mentioning
confidence: 99%